Analogs of Precambrian microbial communities formed de novo in Caucasian mineral water aquifers - Daria G. Zavarzina; Alexey A. Maslov; Alexander Y. Merkel; Nataliya A. Kharitonova; Alexandra A. Klyukina; Ekaterina I. Baranovskaya; Elena A. Baydariko; Evgeniy G. Potapov; Kseniya S. Zayulina; Andrey Y. Bychkov; Nikolay A. Chernyh; Elizaveta A. Bonch-Osmolovskaya; et al. (mBio)
ABSTRACT The microbiome of deep continental aquifers is considered the most slowly evolving part of the biosphere. The Yessentukskoye Mineral Water Basin (YMWB), located in the pre-Caucasus region, contains three closely spaced but distinct aquifers, the Upper Cretaceous, the Lower Cretaceous, and the Upper Jurassic, which represent unique objects for subsurface biosphere research due to gas-hydrogeochemical and thermal anomalies of the area. We analyzed the geological and hydrogeochemical parameters of the three aquifers and a recharge area of the YMWB and investigated their microbial communities using metagenomic and cultivation-based approaches within a long-term survey. Correlation analysis of the obtained data revealed stable and highly stratified microbial communities inhabiting four distinct ecosystems. Their structure and the metabolic traits of their prokaryotic populations were similar to those presumed to have dominated the Earth’s biosphere during several critical periods of its evolutionary history, that is, the Early Archean, the period of banded iron formations accumulation, and the Great Oxidation Event. Among the YMWB strata, the Upper Jurassic aquifer, supersaturated with CO2, influenced by magmatic activity, and highly enriched with thermophilic autotrophic hydrogenotrophic acetogens, turned out to be the first described modern ecosystem based on the primary production by a process predicted to support the Last Universal Common Ancestor (LUCA). The characterization of the YMWB microbial communities reveals a contemporary model environment of the early stages of Earth’s development and thus contributes to the understanding of the evolutionary traits in microbial populations that may have played a critical role in the formation of the modern biosphere.IMPORTANCEContinental subsurface environments are estimated to harbor up to one-fifth of the planet’s total biomass, representing the most stable and slowly evolving part of the biosphere. Among the deep subsurface inhabitants, the microbial communities of drinking mineral waters remain the least studied. Our interdisciplinary study of the Yessentukskoye Mineral Water Basin shows how hydrochemical and hydrodynamic factors shape different subsurface ecosystems, whose microbial populations influence the composition of mineral waters. A comprehensive analysis reveals the similarity of these ecosystems to those predicted for the early Earth. The deepest of the studied aquifers is the first described modern ecosystem with the most probable primary producer performing hydrogenotrophic acetogenesis. Thus, our results contribute to the understanding of the genesis of modern drinking water resources and expand the knowledge of the evolutionary traits that may have played a critical role in the formation of the Earth’s biosphere.